Determinants of firm value: Firm size as a moderating variable - Sri Ayem; Yohana Eksen Seseng (Journal of Business and Information Systems (e-ISSN: 2685-2543), 2026)
The purpose of this study is to determine whether profitability, managerial ownership, and ESG disclosure directly influence firm value and whether firm size influences these factors. The subjects of this study were mining companies listed on the Indonesia Stock Exchange (IDX) between 2021 and 2024. The research data consisted of secondary data (audited figures) in the form of financial reports, annual reports, or sustainability reports obtained from various company websites, www.idx.co.id, and company websites for the years 2021–2024. The sample collection method used was purposive sampling, resulting in the selection of 72 companies that met the criteria. The methodology used in this study is quantitative and employs a single measurement item. SEM-PLS 4.0 stands for Structural Equation Modeling-Partial Least Squares. The research findings indicate that profitability and managerial ownership have a positive and significant impact on firm value, while ESG development does not. Furthermore, firm size, as a moderating factor, does not influence the effect of profitability on firm value. Despite this, it has been established that firm size negatively impacts managerial ownership. However, firm size may increase the impact of ESG on firm value.